GOLEK AYUN-AYUN DANCE AS A REALIZATION OF JAVA PHILOSOPHY IN HERMENEUTIC PERSPECTIVE - Risa Kaizuka (Imaji, 2020)
This article aims to see the Golek Ayun-Ayun dance as a manifestation of Javanese philosophyfrom a hermeneutic perspective. The way of writing is by interpreting the Golek Ayun-Ayundance performance elements, starting from elements of dance movements to elements of clothing.The results of this writing indicate that the Golek Ayun-Ayun dance is a dance that is not stagedfor entertainment only, but this dance has a Javanese philosophical meaning from movement,clothing, to decoration. The manifestations are: (1). The Sembahan movement (forward beksan)with the position of joining the hands and thumbs affixed in front of the chest is a symbol ofgreeting horns to God, the Sultan, and the guests so that the attitude of this dance is to maintaingood manners, tolerance, and respect for others. (2). The batik cloth of the parang rusak with thegurdha machete motif is a symbol of adoration. (3). The Jamang Elar decoration is a headbandgiven a variety of menthog feathers as a symbol of a girl in bloom. Golek Ayun-Ayun dance hasexcellent characteristics (high quality) and many layers of meaning.Keywords: Golek Ayun-Ayun dance, meaning, Javanese philosophy